A Case Study for Technical and Vocational Education and Training Professional Development Training in Untact Era: Focusing on Official Development Assistance Project in Botswana - Lee, Youngmin; Kim, Woocheol; Woo, Heajung (Journal of Technical Education and Training, 2021)
The prolonged COVID-19 pandemic has disrupted the TVET professional development training, which was planned to be carried out in a face-to-face manner. This study aims to examine TVET professional development training based on the ADDIE model and provide implications for ODA and TVET professional development training in the post-COVID era. In this case study, a TVET training program for Botswana was developed based on the ADDIE model in an untact environment. Accordingly, the performance activities for each phase of analysis, design, development, implementation, and evaluation were analyzed, and based on this, implications for ODA and TVET were provided. This study identified the applicability of non-face-to-face education in the ODA project. Also, this study explored how to develop systematic and dimensional programs based on the ADDIE model in a non-face-to-face manner. In addition, sustainability could be secured through cooperative partnerships between donor and beneficiary countries from the perspective of SDGs Goal.